A comparison of differential reinforcement procedures for treating automatically reinforced behavior. Issue 1 (26th April 2019) - Hedquist, Chelsea B.; Roscoe, Eileen M.
Abstract : Children diagnosed with autism spectrum disorder (ASD) often exhibit stereotypy, which can be socially stigmatizing, interfere with daily living skills, and affect skill acquisition. We compared differential reinforcement of alternative behavior (DRA) and differential reinforcement of other behavior (DRO) when neither procedure included response blocking or interruption for (a) reducing stereotypy, (b) increasing task engagement, and (c) increasing task completion. DRA contingencies yielded superior outcomes across each measure when evaluated with 3 individuals with autism spectrum disorder.